Pengaruh Rebusan Jahe Terhadap Penurunan Mual Muntah Pada Ibu Hamil Trimester I - Arsi, Ranida; Juwairia, Juwairia; Utama Saputra, Andre (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
The first trimester of pregnancy affects physical changes in a woman. During pregnancy, the hormones estrogen, progesterone, and human chorionic gonadotropin fluctuate, causing nausea and vomiting. Nausea and vomiting are conditions that usually appear starting at 4 weeks of pregnancy and ending at 16 weeks of pregnancy. Ginger is an alternative to overcome nausea and vomiting in pregnant women. The first advantage of ginger is the content of essential oils that are refreshing and inhibit the gag reflex so that blood circulation and nerves work properly. This study aims to determine the effect of boiled ginger on reducing nausea and vomiting in pregnant women in the first trimester. This study used a quasi-experimental method with a non-equivalent with control group design. In this design, the subjects were divided into two groups, namely the experimental group given ginger and the control group given water. Respondents were 54 pregnant women who experienced nausea and vomiting who were divided into 2 groups. The results of the study found that there was a significant difference in the frequency of nausea and vomiting in pregnant women before and after being given ginger decoction in the experimental group with a p value = 0.000 and there was a significant difference in the frequency of nausea and vomiting in pregnant women before and after being given water in the control group with a p value = 0.000. There was no difference in the effectiveness of reducing the frequency of nausea and vomiting in the experimental group and the control group with a value of (p = 0.831). It is hoped that this research can be a reference and can be applied to pregnant women to reduce nausea and vomiting, especially in pregnant women in the first trimester